Pengaruh Fraud Pentagon Terhadap Fraudulent Financial Statement dengan Umur Perusahaan Sebagai Variabel Moderasi - Noviani, Witria; Nofryanti (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to analyze and provide empirical evidence of the influence of the fraud pentagon which consists of the components of pressure, opportunity, rationalization, ability and arrogance on fraudulent financial statements, moderated by company age. The research was conducted using a purposive sampling method on 63 industrial sector companies listed on the Indonesia Stock Exchange in 2018-2022. A sample of 24 companies was obtained, then outliers were carried out for 8 companies, resulting in the final sample data remaining in this study being 80 data. The research results concluded that pressure had an effect on fraudulent financial statements, while opportunity, rationalization, ability and arrogance had no effect. The moderating variable company age cannot weaken the influence of pressure, opportunity, rationalization, ability and arrogance on fraudulent financial statements. Meanwhile, simultaneously it shows that the variables as a whole have an influence on fraudulent financial statements.